A systematic review with meta-analysis of the role of anxiety and depression in irritable bowel syndrome onset. Issue 15 (8th September 2016) - Sibelli, A.; Chalder, T.; Everitt, H.; Workman, P.; Windgassen, S.; Moss-Morris, R.
Abstract : Background: It is well established that people with irritable bowel syndrome (IBS) have higher levels of anxiety and depression compared with controls. However, the role of these as risk factors is less clearly established. The aims of this systematic review were to investigate: (1) whether anxiety and/or depression predict IBS onset; (2) the size of the relative risk (RR) of anxiety versus depression in IBS onset. Subgroup analyses explored if methodological factors affected the overall findings. Method: Prospective cohort or case–control studies were included if they: (1) focused on the development of IBS in population-based or gastroenteritis cohorts; (2) explored the effects of anxiety and/or depression at baseline as predictors of IBS onset at a future point. In all, 11 studies were included of which eight recruited participants with a gastrointestinal infection. Meta-analyses were conducted. Results: The risk of developing IBS was double for anxiety cases at baseline compared with those who were not [RR 2.38, 95% confidence interval (CI) 1.58–3.60]. Similar results were found for depression (RR 2.06, 95% CI 1.44–2.96). Anxiety and depression seemed to play a stronger role in IBS onset in individuals with a gastrointestinal infection although this could be attributed to other differences in methodology, such as use of diagnostic interviews rather than self-report. Conclusions: The findings suggest that self-reported anxiety and depression provide a twofold risk for IBS onset. There is less support for the role of anxiety or depressive disorder diagnosed using clinical interview. These findings may have implications for the development of interventions focused on IBS prevention and treatment.